A survey of the governance capacity of national public health associations to enhance population health - James Chauvin; Mahesh Shukla; James Rice; Laetitia Rispel (BMC, 2016)
Abstract Background National public health associations (PHAs) are key partners with governments and communities to improve, protect and promote the public's health. Governance and organizational capacity are among the key determinants of a PHA's effectiveness as an advocate for appropriate public health policies and practice. Methods During 2014, the World Federation of Public Health Associations (WFPHA) conducted an on-line survey of its 82 PHA members, to identify the state of organizational governance of national public health associations, as well as the factors that influence optimal organizational governance. The survey consisted of 13 questions and focused on the main elements of organizational governance: cultivating accountability; engaging stakeholders; setting shared direction; stewarding resources; and, continuous governance enhancement. Four questions included a qualitative open-ended response for additional comments. The survey data were analyzed using Microsoft Excel. The qualitative data was analyzed using thematic content analysis Results Responses were received from 62 PHAs, constituting a 75.6 % response rate. The two most important factors that support governance effectiveness were a high degree of integrity and ethical behavior of the PHA's leaders (77 %) and the competence of people serving on the PHA's governing body (76 %). The lack of financial resources was considered as the most important factor that negatively affected organizational governance effectiveness (73 %). The lack of mentoring for future PHA leaders; ineffective or incompetent leadership; lack of understanding about good governance practices; and lack of accurate information for strategic planning were identified as factors influencing PHA governance effectiveness. Critical elements for PHA sustainability included diversity, gender-responsiveness and inclusive governance practices, and strategies to build the future generation of public health leaders. Conclusion National PHA have a responsibility to put into place the practices and infrastructure that enhance organizational governance. This will enhance their ability to be effective advocates for policies and practices that enhance, protect and promote the public's health. The WFPHA has an important role to play in providing the technical assistance and financial resources to assist PHAs in attaining and sustaining a higher level of governance capacity.